RENDIMENTO DO PROCESSAMENTO DOS PRODUTOS ORIUNDOS DA FIBRA VEGETAL DA PIAÇAVA (Attalea funifera) (Nativa, 2020)
O presente trabalho abordou uma análise integrada do processamento dos Produtos Florestais Não Madeireiros (PFNM) oriundos da fibra vegetal junto aos diversos atores da cadeia produtiva da piaçava da Bahia (Attalea funifera Mart. Arecaceae). Atualmente a renda média do agroextrativista é aproximadamente R$ 600,00/mês no sistema convencional. Neste caso as fibras vegetais são processadas e comercializadas nas formas: bruta, limpa, cortada, fino-média e grosso-média. Para obtenção de uma análise integral da cadeia produtiva, a metodologia empregada consistiu em: ensaios de rendimento em seis sistemas produtivos diferentes e entrevistas com gestores, diálogos com produtores e agroextrativistas tradicionais. Os resultados do processamento da fibra vegetal apontaram que 47,3% de resíduos são descartados, 35,6% são fibras fino-média, 5,3% grosso-média e 17% de “fita” são aproveitadas. Os ganhos do agroextrativista, supondo um cenário em que todas as etapas do processo produtivo de confecção das vassouras de piaçava fossem realizadas, corresponderiam a uma renda mensal líquida de R$ 1.664,63, muito acima da renda média atual.Palavras-chave: fibras naturais; produtos florestais não madeireiros (PFNMs); piaçava da Bahia; agroextrativismo; Mata Atlântica; resíduos florestais. YIELD OF THE PRODUCTS PROCESSING FROM THE VEGETABLE FIBER OF PIASSAVA PALM TREE (Attalea funifera) ABSTRACT: This article point out an integrated analysis of the processing of non-timber forest products (NTFPs) originating from the vegetable fiber with the different actors of the productive chain of the piassava palm tree of Bahia (Attalea funifera Mart. Arecaceae). Currently the average income of the of the agroextractivist is approximately US$ 256,13 per month in the conventional system. In that case, the vegetable fibers are processed and commercialized in the forms: raw fiber, clean fiber, cut fiber, thin-medium fiber and thick-medium fiber.  In order to obtain complete analysis of piassava palm tree production chain, the methodology used consisted of: performance tests in six different production systems, the interviews with managers and dialogues with traditional producers and agroextractivists. The results of the processing of the vegetable fiber indicated that 47,3 % of the residues are discarded, 35,6% are thin-medium fibers, 5,3% thick-medium fibers and 17% of “stripes” (by-product) are used. The gains of the agroextractivist, supposing scenario in which all stages of the production process of making the piassava brooms were held, would be followed, might correspond to a monthly net reve nue of US$ 710,59 well above the current average yield.Keywords: natural fibers; Non-timber forest products (NTFPs); Bahia piassava; Atlantic forest; Exploitation of forest residues.